The power of personalization: using a personalized storybook depicting a cross-group friendship to improve White children’s attitudes, feelings, and behaviors toward Black and Hispanic peers - Wadian, Taylor W. (Kansas State University, 2017)
In the current study, 141 White third- and fourth-grade children were asked to provide their attitudes, feelings, and behaviors toward White, Black, and Hispanic peers several days before and after being read a personalized or non-personalized storybook that depicted the children, themselves (personalized) or an unfamiliar White character (non-personalized), in a cross- or same-race friendship with a target Black (cross-race) or White (same-race) storybook character. Further, children were asked to provide their attitudes, feelings, and behaviors toward the target Black or White storybook character immediately before and after being read the storybook, and report how much they felt imaginatively transported into the narrative of the story after being read the storybook. In general, and consistent with Harwood’s (2010) two-dimensional framework of contact space, it was predicted that a personalized storybook that depicted the children, themselves, in a cross-race friendship with a Black storybook character would be more effective than a non-personalized version of the storybook at improving their ratings of the Black storybook character as well as their attitudes, feelings, and behaviors toward the Black and Hispanic peers. Although analyses of the data yielded several interesting findings, no support was found for the main predictions involving the potential impact of a personalized storybook on White children's ratings of the Black storybook character, Black peers, and Hispanic peers. In fact, the only significant effect of the personalization of the storybook that merits attention involved the children’s imaginative transportation into the cross-race friendship story. Specifically, and consistent with prediction, children in the cross-race friendship storybook condition reported feeling more imaginatively transported into the narrative of the storybook when it was personalized than when it was not personalized. In sum, although personalization was indeed “powerful” in elevating White children’s imaginative transportation into a storybook that depicted a cross-race friendship, it was not powerful enough to influence their attitudes, feelings, and behaviors toward the Black storybook character, the Black peers, or the Hispanic peers. The implications and limitations of the present study, as well as directions for future research, are addressed.
Keywords: Intergroup contact; Prejudice; Intergroup relations; Children